Applying to Make A Match Strategy in Social Studies Subjects as an Effort to Improve Student Learning Outcomes for Class VIII.A SMP Negeri 10 Kendari - Wa Ode Nurhafiah (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2022)
This study aimed to improve student learning outcomes in social studies by using the make-a-match learning strategy. This Classroom Action Research uses subjects and data sources for class VIII. A student of SMP Negeri 10 Kendari for the academic year 2021/2022 in social studies subjects with 40 students. The research design used is the flow method from Kemmis and Taggart with a cycle model. They are collecting research data using observation techniques and learning outcomes tests. The data analysis procedure used interactive model analysis from Melles and Huberman. Based on the analysis of test results and findings in the reflection-evaluation of learning activities, 1) through appropriate procedures and steps, the application of the make-a-match strategy can improve student learning outcomes in social studies subjects; 2) The application of this strategy can increase students' active participation in the teaching and learning process which can be seen from the increasing value of students' active participation in learning, such as cooperation, the focus of attention, time efficiency, suitability of results, and presentations; 3) The percentage and number of students who scored above the KKM reached more than 85%; and 4) students' perceptions of the use of the make a match strategy applied in this study were very positive, most students expressed pleasure if this strategy was used in presenting other material on social studies subjects. This strategy effectively improves student learning outcomes when learning is understood about the steps in using the strategy, the teacher guides students who encounter difficulties in the learning process, and at the end of the lesson, an evaluation test is given and reflects on learning.